Nothing ever dies : Vietnam and the memory of war - Nguyen, Viet Thanh (Harvard University Press, 2016)
"All wars are fought twice, the first time on the battlefield, the second time in memory. Exploring how this troubled memory works in Vietnam, the United States, Laos, Cambodia, and South Korea, the book deals specifically with the Vietnam War and also war in general. He reveals how war is a part of our identity, as individuals and as citizens of nations armed to the teeth. Venturing through literature, film, monuments, memorials, museums, and landscapes of the Vietnam War, he argues that an alternative to nationalism and war exists in art, created by artists who adhere to no nation but the imagination."--Provided by publisher.
Keywords: Vietnam War, 1961-1975 : Social aspects; Vietnam War, 1961-1975 : Art and the war; Memory : Sociological aspects; War and society; Art and war; Identity (Psychology) in art; Vietnamin sota; yhteiskunnalliset vaikutukset; kollektiivinen muisti; sodat; identiteetti; taide